Fine needle aspiration of renal cortical lesions in adults - Adeniran, Adebowale J.; Al-Ahmadie, Hikmat; Iyengar, Pratibha; Reuter, Victor E.; Lin, Oscar (Diagnostic cytopathology, 2010)
The role of fine needle aspiration (FNA) biopsy of renal cortical lesions was controversial in the past because the result of the FNA did not affect clinical management. All renal cortical lesions, except metastasis, were subject to surgical resection. However, with the advances in neoadjuvant targeted therapies, knowledge of the renal cortical tumor histological subtype is critical for tailoring clinical trials and follow‐up strategies. At present, there are clinical trials involving the use of novel kinase inhibitors for conventional (clear cell) and papillary renal cell carcinoma. We studied 143 consecutive cases of renal cortical lesions, evaluated after radical or partial nephrectomies over a 2‐year period. An air‐dried smear and a Thinprep® slide were prepared in all cases. The slides were Diff‐Quick and Papanicolaou stained, respectively. The cytology specimens were reviewed and the results were then compared with the histologic diagnosis. Cytology was highly accurate to diagnose conventional RCC, while the accuracy for papillary RCC, chromophobe RCC, and papillary urothelial carcinoma was much lower. Our results indicate that ancillary studies might have an important role in the subclassification of renal cortical neoplasms for targeted treatment. Diagn. Cytopathol. 2010;38:710–715. © 2009 Wiley‐Liss, Inc.